Developing the library of Bagong Ilog Elementary School in Pasig City - Silvestre, Camille Jol P.; Dorado, Dan Anthony D.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Developing the library of Bagong Ilog Elementary School was created to respond to the needs of its learners. The library has limited resources and the most of its books are outdated. Also, the library does not have a licensed librarian to manage the site which results to its unorganized collection of resources.
The project focuses on three objectives: (a) To create a manual on library operations which includes the library's vision, mission, objectives, policies and procedures. (b) To acquire library resources. (c) To organize the collection based on Dewey Decimal Classification system.
The project manager conducted school and library visitation to observe and interview the principal and the teacher-librarian with regards to the library operations. Based on the interview and assessment, the library does not meet the standards for school libraries created by DepEd. Likewise, a survey was also conducted to the students c/o the teacher librarian in coordination with the faculty to identify the needs of the users.
The creation of the manual was used to determine library operation to be followed to have an operational library. The project manager also solicited library materials and funds from suppliers, friends, and family, materials such as reference books, children's books, educational board games and play mats were given by the donors for this project. Funds collected were used to purchase books as additional materials to the library. Lastly, to properly organize the collection, the project manager used a color coded Dewey Decimal Classification scheme in which the collections were arranged and labeled.
The results of this project well be beneficial to the enrichment of the 21st century skills of the students of Bagong Ilog Elementary School. This project encourages lifelong learners through its collection and resources offered by the developments applied and integrated to the library.
Special Problem (Master of Library and Information Science)
Keywords: Library development -- Bagong Ilog Elementary School -- Pasig City